ALCALA, Victoria, Susana Thénon. Loba esteparia, Buenos Aires, Ediciones Lamas Médula, 2020, 164 pp. - Tamai, Agustín Francisco (Letras, 2021)
Reseña de Alcala, Victoria, Susana Thénon. Loba esteparia, Buenos Aires, Ediciones Lamas Médula, 2020, 164 pp.